Message from the Grassroots: Scholarly Communication, Crisis, and Contradictions - Noûs, Camille Marcos (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
Librarians have responded to the decades-long “serials crisis” with a common narrative and a range of responses that have failed to challenge the ideology and structures that caused it. Using Walter Rodney’s theory of a guerilla intellectual, we critically examine the dominant understanding of this so-called crisis and emphasize the role that capital plays within it. The imperial nature of scholarly journal publishing and some of its many contradictions are discussed. “Transformative” agreements receive special attention as a hyper-capitalist manifestation of these contradictions at the heart of commercial publishing.The politics of refusal are one response to the commercialism, prestige, and power imbalances that drive the academic publishing system. Highlighting the differences between refusal and reform, this paper explores the protagonistic role that librarians can play in a protracted struggle within and beyond the confines of our profession. Select open access efforts are identified at the end as examples of different forms of refusal. This paper is intended to move beyond the traditional discourse of laying blame solely at the feet of the academic publishing oligopoly and also expounds on the bourgeois academy’s use of knowledge production for capital accumulation.